TINJAUAN HUKUM PERJANJIAN KERJA LAUT ANTARA PERUSAHAAN PELAYARAN DENGAN NAHKODA ATAS PENGOPERASIAN KAPAL - Sabardin, Sabardin; Rahman, Muhammad Sabir; Syahril, Muh. Akbar Fhad; Wiwin, Wiwin; Tijjang, Bakhtiar (Jurnal Ilmiah Dinamika Hukum, 2025)
This study analyzes the legal position of the captain in the structure of maritime employment relations with a case study at PT. Kembang Mekar Indah, which highlights the gap between the normative provisions in the Commercial Code (KUHD), Law Number 17 of 2008 concerning Shipping, and the Maritime Labor Convention (MLC) 2006 with the implementation practices in the field. This study uses a normative-empirical legal method through literature studies and interviews with captains and company representatives, analyzed qualitatively-descriptively to compare legal norms and empirical reality. The results of the study indicate that maritime employment agreements still place captains on an equal footing with ordinary workers even though the legislation confirms their position as the highest leader on board and the legal representative of the ship owner. Empirical findings show that the fulfillment of the captain's rights to salary is 80%, work facilities 60%, legal protection 40%, and regulatory socialization only 20%, indicating an imbalance in legal protection and weaknesses in the substance of the employment contract. Therefore, it is necessary to reformulate the shipping legal system by improving maritime work agreements, strengthening the role of harbormasters, and harmonizing national regulations with the 2006 MLC standards in order to create maritime work relations that are professional, fair, and adaptive to international maritime law.